ANALYSIS OF DATA EXCHANGE ARCHITECTURES AND MULTIMEDIA TECHNOLOGIES - Zalužinskis, Artūrs; Tabors, Edgars; Zarembo, Imants (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The main objectives of the research work are to classify information systems by the field of usage and to analyze the data exchange architectures and multimedia technologies for successful development process of electronic information systems. The main data exchange architectures are described, the possible methods of interconnection possibilities of technologies are analyzed.